Electromyographic Changes in Thyrotoxicosis - Mussa, Khalid I. (Journal of the Faculty of Medicine Baghdad, 2007)
Objectives: To document electromyographic changes in thyrotoxic patients, and to categorize the type of myopathic process in thyrotoxicosis. Design: This case control study was designed to show the electromyographic changes in thyrotoxic patients and to compare these findings with that of normal aged matched controls to show the significance of these changes in thyrotoxic patients. Student’s test was applied on the results and P value was extracted. Subjects: Subjects in this study were chosen according to certain criteria depending mainly on their blood level of thyroid hormone (T3, and T4) and TSH. All of them are thyrotoxic patients, their ages range between 15 to 45 years. They were 25 patients (15 female and 10 males). Another 25 subjects were chosen as normal controls they were of the same age and sex, patient with features of myopathy or neuropathy from diseases other than thyrotoxicosis were excluded carefully from studied patients and the normal controls. Results: EMG finding in thyrotoxic patients was as follows: No spontaneous activities in the proximal muscles (deltoid and in rectus femoris muscles). The amplitude of the motor unit action potentials was ranging between (200-800 microv) with a mean of (488.8 +/- 159.3microv.) in the deltoid muscle, while the amplitude of the action potential In rectus femoris muscle in thyrotoxic patients was ranging between (350-900 microv.). In abductor pollicis brevis muscle the action potential amplitude in thyrotoxic patients was ranging between (500-2150 microv.), there was significant difference between thyrotoxic patients and normal controls. The duration of the motor unit potential in thyrotoxic patients was ranging between (7—11.5 msec.) with a mean of (8.51+/- 1,24 msec) in the deltoid muscle, slightly higher figures in rectus femoris muscle, this indicates significant difference in the duration of action potential between patients and normal controls. The other parameters of EMG study all indicate a myopathic process involving proximal muscles in 76% of thyrotoxic patients and a neuropathic process involving distal muscles in 28% of thyrotoxic patients. Conclusions: 1-thyrotoxicosis involves proximal muscles more than distal muscles. 2-myopathic process in thyrotoxicosis can be observed clearly in EMG study of the proximal muscles. 3-EMG findings in thyrotoxic myopathy includes, short duration polyphasic potentials, with early recruitment full interference pattern. 4-Distal muscles in thyrotoxic patients may show EMG findings of a rather neuropathic process.